Potensi Ekstrak Daun Kirinyuh (Chromolaena odorata) dalam Menghambat Bakteri Patogen (E. sakazakii, S. typi, dan L. monocytogenes) - Khotibul Umam; Linda Wulandari (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Kirinyuh (Chromolaena odorata) is one of the wild plants found that is difficult to eradicate because it has a high defense, so this plants is considered a weed plant that is detrimental to farmers and planters. However, the kirinyuh plant has the potential to be developed as an antibacterial. One of the natural ingredients that show pharmacological effects is flavonoids. This study aims to determine the antibacterial activity, and the effective concentration of kirinyuh extract in inhibiting the growth of Enterobacter sakazakii, Salmonellla typi, and Listeria monocytogenes bacteria. To get the extract used extraction method by maceration of immersion using 96% ethanol as solvent. The concentration of kirinyuh extract used was 20%, 40%, 60%, 80%, and 100%. While the positive control was used Ampicillin and negative control was used ethanol 96%, and for testing the antibacterial activity was carried out using the well difsusion method. The results of the antibacterial activity test were analyzed using ANOVA with a 95% confidance level and continued with Duncan’s Multiple Range Test (DMRT). The results showed that the extract concentrations of 20%, 40%, 60%, 80%, and 100% had given inhibitory activity to the growth of the test bacteria. At a concentration of 100%, kirinyuh extract was more effective as an antibacterial against bacteria Enterobacter sakazakii, Salmonella typi, and Listeria monocytogenes bacteria compared to other concentrations. The increase in the concentration of kirinyuh extract showed the larger the diameter of the inhibition zone for bacterial growth. The results of the inhibitory power test of kirinyuh extract against bacteria Enterobacter sakazakii with an average value of the inhibition zone of 6,66 mm, and against Salmonella typi the average value of the inhibition xone was 4,83 mm, and Listeria moncytogenes with an average value of 5, 60 mm.